Composition containing p-tert-butylbenzoic acid and application of composition in preparation of fully synthetic cutting fluid

By using a composition containing para-tert-butylbenzoic acid in the fully synthesized cutting fluid, combining modified nanomaterials and modified walnut shells to form a protective film, the metal processing fluid is solved to prevent rust and lubrication after storage at high temperature or long time. The problem of performance degradation has achieved better anti-rust effect and lubrication performance.

CN119242375APending Publication Date: 2025-01-03SANHE RUNYI NEW MATERIALS (GUANGZHOU) CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411395042.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing fully synthetic metal processing liquid is prone to yellowing and turbidity after high temperature or long-term storage, resulting in a decrease in its anti-rust and lubricating performance during metal processing.

Method used

Using a composition containing para-tert-butylbenzoic acid, a protective film on the metal surface is formed by adding a modified nanomaterial and modified walnut shell, which prevents contact between air and moisture, enhances lubricity and rust resistance. , and improve the stability and uniformity of the cutting fluid through modification treatment.

Benefits of technology

This composition can effectively prevent metal corrosion, improve lubrication performance, extend the service life of workpieces and machine tools, and maintain the anti-corrosion and rust effect of cutting fluid during processing, reduce the amount of fatty acids, and enhance lubricity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention provides a composition containing p-tert-butylbenzoic acid and application of the composition in preparation of a fully synthetic cutting fluid. The composition is prepared from the following components in parts by weight: 2 to 4 parts of sodium dodecyl benzene sulfonate, 1 to 2 parts of glycerol, 1 to 2 parts of polyisobutene, 5 to 7 parts of modified walnut shell, 3 to 4 parts of ammonium molybdate, 1 to 2 parts of polyethylene glycol, 2 to 4 parts of diethanol amine, 1 to 3 parts of oleic acid, 4 to 6 parts of p-tert-butylbenzoic acid, 5 to 6 parts of monoethanolamine benzoate, 0.06 to 0.18 part of sodium lauryl sulfate and 12 to 13 parts of polyvinyl chloride latex. 3-5 parts of tetrazole, 1-2 parts of a modified nano material and 200 parts of deionized water. The composition has good cooling performance, greatly takes away heat generated in the machining process, is good in lubricity and anti-rust performance and is suitable for metal machining of various types.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of cutting fluids, and in particular relates to a composition containing p-tert-butylbenzoic acid and application of the composition in preparing a fully synthetic cutting fluid. Background Art

[0002] Cutting fluids are liquids used for cooling and lubrication during metalworking. They play a vital role in machining, helping to reduce friction between the tool and the workpiece, taking away heat, and helping to remove chips and prevent small chips from scratching the machined surface. Currently, fully synthetic metalworking fluids generally turn yellow and become turbid after being stored at high temperatures or for a long time.

[0003] Therefore, there is an urgent need for a composition containing p-tert-butylbenzoic acid and its application in preparing a fully synthetic cutting fluid. Summary of the invention

[0004] The purpose of the present invention is to provide a composition containing p-tert-butylbenzoic acid and application of the composition in preparing a fully synthetic cutting fluid.

[0005] In order to achieve the above object, the present invention provides the following technical solutions: A composition containing p-tert-butylbenzoic acid comprises the following components in parts by weight: 2-4 parts of sodium dodecylbenzene sulfonate, 1-2 parts of glycerol, 1-2 parts of polyisobutylene, 5-7 parts of modified walnut shells, 3-4 parts of ammonium molybdate, 1-2 parts of polyethylene glycol, 2-4 parts of diethanolamine, 1-3 parts of oleic acid, 4-6 parts of p-tert-butylbenzoic acid, 5-6 parts of monoethanolamine benzoate, 0.06-0.18 parts of sodium lauryl sulfate, 12-13 parts of polyvinyl chloride latex, 3-5 parts of tetrazole, 1-2 parts of modified nanomaterials and 200 parts of deionized water.

[0006] Furthermore, the preparation method of the modified nanomaterial is: (1) Mix 1 part of nanomaterial with 10-12 parts of water, add sodium carbonate to make the pH value 9-10, and stir at 60-64°C for 2-3 hours to form a nanomaterial suspension; (2) Add 0.2-0.4 parts of hexadecyltrimethylammonium bromide to 10 parts of the nanomaterial suspension, mix well, stir, react at 55-60° C. for 2-3 hours, filter, wash, dry, and grind to obtain a modified nanomaterial.

[0007] Furthermore, the nanomaterials are nano-aluminum oxide, nano-silicon carbide and nano-lanthanum oxide in a mass ratio of 1:1.2-1.3:0.6-0.7.

[0008] Furthermore, the preparation method of the modified walnut shell is: (1) crushing dried walnut shells, adding them to a sodium hydroxide aqueous solution 5-6 times the mass of the walnut shells, heating them to 125-130° C. at a pressure of 0.26-0.29 MPa and keeping the temperature for 120-130 minutes to obtain a first solution; (2) After the first solution is cooled to 65-70° C., a sulfuric acid aqueous solution in an amount 3-4 times the mass of the walnut shells is added thereto, and the solution is kept warm for 35-40 minutes at a pressure of 0.26-0.28 MPa to obtain a second solution; (3) washing the second solution with deionized water until it is neutral, centrifuging, and drying to obtain the initially treated walnut shells; (4) The walnut shells after the initial treatment are moistened with water and placed in a microwave field for microwave treatment to obtain modified walnut shells.

[0009] Further, the dried walnut shells are crushed to 200-300 meshes.

[0010] Further, the concentration of the sodium hydroxide aqueous solution is 37-39%.

[0011] Further, the concentration of the aqueous sulfuric acid solution is 43-48%.

[0012] Further, centrifuge at 2300-2500 r / min for 3-5 min.

[0013] Further, the mixture was treated with a microwave at 350-400 W for 2-3 min.

[0014] The invention provides application of a composition containing p-tert-butylbenzoic acid in preparing a fully synthetic cutting fluid.

[0015] Compared with the prior art, the advantages and beneficial effects of the present invention are as follows: after the composition of the present invention contacts the metal, a protective layer is formed on the metal surface, which can block the corrosion of the metal by air; it has good cooling performance, greatly removes the heat generated during the processing, has good lubricity and anti-rust performance, and is suitable for various metal processing. The composition of the present invention is used to prepare a fully synthetic cutting fluid that resists yellowing, has solubilization (reducing the amount of fatty acid used), and enhances lubricity. DETAILED DESCRIPTION

[0016] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0017] Example 1 The present embodiment provides a composition containing p-tert-butylbenzoic acid, which includes the following components in parts by weight: 3 parts of sodium dodecylbenzene sulfonate, 1.5 parts of glycerol, 1.3 parts of polyisobutylene, 6 parts of modified walnut shells, 3.6 parts of ammonium molybdate, 1.4 parts of polyethylene glycol, 3 parts of diethanolamine, 2 parts of oleic acid, 5 parts of p-tert-butylbenzoic acid, 5.4 parts of monoethanolamine benzoate, 0.12 parts of sodium lauryl sulfate, 12.6 parts of polyvinyl chloride latex, 4 parts of tetrazole, 1.4 parts of modified nanomaterials, and 200 parts of deionized water.

[0018] The preparation method of the modified nanomaterial is: (1) Mix 1 part of nanomaterial and 11 parts of water, add sodium carbonate to make the pH value 9.5, and stir at 62°C for 2.4 hours to form a nanomaterial suspension; (2) Add 0.3 parts of hexadecyltrimethylammonium bromide to 10 parts of the nanomaterial suspension, mix well, stir, react at 56° C. for 2.6 hours, filter, wash, dry, and grind to obtain modified nanomaterials.

[0019] The nanomaterials are nano-aluminum oxide, nano-silicon carbide and nano-lanthanum oxide in a mass ratio of 1:1.2:0.7.

[0020] There are many reasons why the modified nanomaterials added to the cutting fluid can improve the anti-corrosion and anti-rust effects. The modified nanomaterials have a large specific surface area and high activity, and can form a tight protective film on the metal surface. This protective film can effectively isolate oxygen and moisture in the air, prevent them from directly contacting the metal surface, thereby reducing the possibility of corrosion. The nanomaterials can maintain a good dispersion state in the cutting fluid, so that the stability and uniformity of the cutting fluid are improved. This helps to maintain the uniform distribution of the effective ingredients of the cutting fluid during the processing, thereby improving its anti-corrosion and anti-rust effects. The surface of the modified nanomaterial contains specific functional groups (for example, through surfactant treatment), which can react chemically with the metal surface to generate a dense passivation layer, prevent the penetration of corrosive media, and play an anti-corrosion role. The nanomaterial can also improve the lubrication performance of the cutting fluid, reduce the friction and wear between the tool and the workpiece, and indirectly protect the metal surface from damage, thereby reducing the probability of corrosion. Through the modification treatment of surfactants such as hexadecyltrimethylammonium bromide (CTAB), the surface properties of the nanomaterial are optimized, making it easier to adhere to the metal surface and form a more effective protective layer.

[0021] The preparation method of modified walnut shell is: (1) crushing dried walnut shells, adding them to a sodium hydroxide aqueous solution 6 times the mass of the walnut shells, heating them to 128° C. at a pressure of 0.27 MPa and keeping the temperature for 125 min to obtain a first solution; (2) After the first solution is cooled to 67° C., a sulfuric acid aqueous solution in an amount 4 times the mass of the walnut shells is added thereto, and the solution is kept warm for 38 minutes at a pressure of 0.27 MPa to obtain a second solution; (3) washing the second solution with deionized water until it is neutral, centrifuging, and drying to obtain the initially treated walnut shells; (4) The walnut shells after the initial treatment are moistened with water and placed in a microwave field for microwave treatment to obtain modified walnut shells.

[0022] The present invention can improve the anti-corrosion and anti-rust effect of cutting fluid by adding modified walnut shell, mainly because after chemical modification, the surface properties of walnut shell are changed, and its adsorption capacity and chemical activity are enhanced. Through the treatment of sodium hydroxide and sulfuric acid, the functional groups (such as hydroxyl, carboxyl, etc.) on the surface of walnut shell may increase, thereby improving its ability to adsorb metal surface. The modified walnut shell can form a protective film on the metal surface to prevent moisture and oxygen from directly contacting the metal surface, thereby inhibiting the occurrence of corrosion reaction. Microwave treatment can make the internal structure of modified walnut shell more loose and increase its surface area, which is also conducive to the walnut shell to absorb more corrosive media, and may promote the reaction between it and the corrosive medium, thereby enhancing the anti-corrosion performance. Natural walnut shell contains certain biologically active ingredients, such as natural antioxidants such as tannic acid, which are still retained after modification. They can be used as natural preservatives and help to improve the overall anti-corrosion effect of cutting fluid. Modified walnut shell can play a good anti-corrosion and anti-rust function in cutting fluid through the above mechanism, thereby extending the service life of workpieces and machine tools and reducing processing quality problems caused by corrosion.

[0023] The dried walnut shells were crushed to 300 mesh.

[0024] The concentration of the sodium hydroxide aqueous solution is 38%.

[0025] The concentration of the aqueous sulfuric acid solution is 45%.

[0026] Centrifuge at 2400 rpm for 4 min.

[0027] The mixture was treated with a microwave at 370 W for 3 min.

[0028] The preparation method of the composition is: (1) Weigh the raw materials of each component according to the above mass percentage and set aside; (2) First, the modified walnut shell, tert-butylbenzoic acid, polyisobutylene and polyvinyl chloride latex were mixed, heated to 52°C, and stirred at a speed of 170 r / min for 18 min until transparent; (3) Then add monoethanolamine benzoate and mix, raise the temperature to 61°C, and stir at a speed of 125 r / min for 9 minutes; (4) Finally, add water and mix, raise the temperature to 62°C, stir at 100 r / min for 4 min, and cool naturally to room temperature.

[0029] Example 2 The present embodiment provides a composition containing p-tert-butylbenzoic acid, which includes the following components in parts by weight: 2 parts of sodium dodecylbenzene sulfonate, 1 part of glycerol, 1 part of polyisobutylene, 5 parts of modified walnut shells, 3 parts of ammonium molybdate, 1 part of polyethylene glycol, 2 parts of diethanolamine, 1 part of oleic acid, 4 parts of p-tert-butylbenzoic acid, 5 parts of monoethanolamine benzoate, 0.06 parts of sodium lauryl sulfate, 12 parts of polyvinyl chloride latex, 3 parts of tetrazole, 1 part of modified nanomaterial, and 200 parts of deionized water.

[0030] The preparation method of the modified nanomaterial is: (1) Mix 1 part of nanomaterial with 10 parts of water, add sodium carbonate to make the pH value 9, and stir at 60°C for 2 hours to form a nanomaterial suspension; (2) Add 0.2 parts of hexadecyltrimethylammonium bromide to 10 parts of the nanomaterial suspension, mix well, stir, react at 55° C. for 2 h, filter, wash, dry, and grind to obtain modified nanomaterials.

[0031] The nano materials are nano aluminum oxide, nano silicon carbide and nano lanthanum oxide in a mass ratio of 1:1.2:0.6.

[0032] The preparation method of modified walnut shell is: (1) crushing dried walnut shells, adding them to a sodium hydroxide aqueous solution 5 times the mass of the walnut shells, heating them to 125° C. at a pressure of 0.26 MPa and keeping the temperature for 120 min to obtain a first solution; (2) After the first solution is cooled to 65° C., a sulfuric acid aqueous solution in an amount three times the mass of the walnut shells is added thereto, and the solution is kept warm for 35 minutes at a pressure of 0.26 MPa to obtain a second solution; (3) washing the second solution with deionized water until it is neutral, centrifuging, and drying to obtain the initially treated walnut shells; (4) The walnut shells after the initial treatment are moistened with water and placed in a microwave field for microwave treatment to obtain modified walnut shells.

[0033] The dried walnut shells were crushed to 200 mesh.

[0034] The concentration of the sodium hydroxide aqueous solution is 37%.

[0035] The concentration of the aqueous sulfuric acid solution is 43%.

[0036] Centrifuge at 2300 r / min for 3 min.

[0037] The mixture was treated with a microwave at 350 W for 2 min.

[0038] The preparation method of the composition is: (1) Weigh the raw materials of each component according to the above mass percentage and set aside; (2) First, the modified walnut shell, tert-butylbenzoic acid, polyisobutylene and polyvinyl chloride latex were mixed, heated to 50°C, and stirred at a speed of 160 r / min for 15 min until transparent; (3) Then add monoethanolamine benzoate and mix, raise the temperature to 60°C, and stir at a speed of 120 r / min for 8 minutes; (4) Finally, add water and mix, raise the temperature to 60°C, stir at 90 r / min for 3 min, and cool naturally to room temperature.

[0039] Example 3 The present embodiment provides a composition containing p-tert-butylbenzoic acid, which includes the following components in parts by weight: 4 parts of sodium dodecylbenzene sulfonate, 2 parts of propylene glycol, 2 parts of polyisobutylene, 7 parts of modified walnut shells, 4 parts of ammonium molybdate, 2 parts of polyethylene glycol, 4 parts of diethanolamine, 3 parts of oleic acid, 6 parts of p-tert-butylbenzoic acid, 6 parts of monoethanolamine benzoate, 0.18 parts of sodium lauryl sulfate, 13 parts of polyvinyl chloride latex, 5 parts of tetrazole, 2 parts of modified nanomaterials, and 200 parts of deionized water.

[0040] The preparation method of the modified nanomaterial is: (1) Mix 1 part of nanomaterial with 12 parts of water, add sodium carbonate to make the pH value 10, and stir at 64°C for 3 hours to form a nanomaterial suspension; (2) Add 0.4 parts of hexadecyltrimethylammonium bromide to 10 parts of the nanomaterial suspension, mix well, stir, react at 60° C. for 3 h, filter, wash, dry, and grind to obtain modified nanomaterials.

[0041] The nanomaterials are nano-aluminum oxide, nano-silicon carbide and nano-lanthanum oxide in a mass ratio of 1: 1.3: 0.7.

[0042] The preparation method of modified walnut shell is: (1) crushing dried walnut shells, adding them to a sodium hydroxide aqueous solution 6 times the mass of the walnut shells, heating them to 130° C. at a pressure of 0.29 MPa and keeping the temperature for 120-130 minutes to obtain a first solution; (2) After the first solution is cooled to 70° C., a sulfuric acid aqueous solution in an amount four times the mass of the walnut shells is added thereto, and the solution is kept warm for 40 minutes at a pressure of 0.28 MPa to obtain a second solution; (3) washing the second solution with deionized water until it is neutral, centrifuging, and drying to obtain the initially treated walnut shells; (4) The walnut shells after the initial treatment are moistened with water and placed in a microwave field for microwave treatment to obtain modified walnut shells.

[0043] The dried walnut shells were crushed to 300 mesh.

[0044] The concentration of the sodium hydroxide aqueous solution is 39%.

[0045] The concentration of the aqueous sulfuric acid solution is 48%.

[0046] Centrifuge at 2500 r / min for 5 min.

[0047] The mixture was treated with a microwave at 400 W for 3 min.

[0048] The preparation method of the composition is: (1) Weigh the raw materials of each component according to the above mass percentage and set aside; (2) First, the modified walnut shell, tert-butylbenzoic acid, polyisobutylene and polyvinyl chloride latex were mixed, heated to 55°C, and stirred at a speed of 180 r / min for 20 min until transparent; (3) Then add monoethanolamine benzoate and mix, raise the temperature to 62°C, and stir at a speed of 130 r / min for 10 min; (4) Finally, add water and mix, raise the temperature to 64°C, stir at 110 r / min for 5 min, and cool naturally to room temperature.

[0049] Comparative Example 1 The difference between this comparative example and Example 1 is that no modified nanomaterial is added.

[0050] A composition containing p-tert-butylbenzoic acid comprises the following components in parts by weight: 3 parts of sodium dodecylbenzene sulfonate, 1.5 parts of glycerol, 1.3 parts of polyisobutylene, 6 parts of modified walnut shells, 3.6 parts of ammonium molybdate, 1.4 parts of polyethylene glycol, 3 parts of diethanolamine, 2 parts of oleic acid, 5 parts of p-tert-butylbenzoic acid, 5.4 parts of monoethanolamine benzoate, 0.12 parts of sodium lauryl sulfate, 12.6 parts of polyvinyl chloride latex, 4 parts of tetrazole and 200 parts of deionized water.

[0051] The preparation method of modified walnut shell is: (1) crushing dried walnut shells, adding them to a sodium hydroxide aqueous solution 6 times the mass of the walnut shells, heating them to 128° C. at a pressure of 0.27 MPa and keeping the temperature for 125 min to obtain a first solution; (2) After the first solution is cooled to 67° C., a sulfuric acid aqueous solution in an amount 4 times the mass of the walnut shells is added thereto, and the solution is kept warm for 38 minutes at a pressure of 0.27 MPa to obtain a second solution; (3) washing the second solution with deionized water until it is neutral, centrifuging, and drying to obtain the initially treated walnut shells; (4) The walnut shells after the initial treatment are moistened with water and placed in a microwave field for microwave treatment to obtain modified walnut shells.

[0052] The dried walnut shells were crushed to 300 mesh.

[0053] The concentration of the sodium hydroxide aqueous solution is 38%.

[0054] The concentration of the aqueous sulfuric acid solution is 45%.

[0055] Centrifuge at 2400 rpm for 4 min.

[0056] The mixture was treated with a microwave at 370 W for 3 min.

[0057] The preparation method of the composition is: (1) Weigh the raw materials of each component according to the above mass percentage and set aside; (2) First, the modified walnut shell, tert-butylbenzoic acid, polyisobutylene and polyvinyl chloride latex were mixed, heated to 52°C, and stirred at a speed of 170 r / min for 18 min until transparent; (3) Then add monoethanolamine benzoate and mix, raise the temperature to 61°C, and stir at a speed of 125 r / min for 9 minutes; (4) Finally, add water and mix, raise the temperature to 62°C, stir at 100 r / min for 4 min, and cool naturally to room temperature.

[0058] Comparative Example 2 The difference between this comparative example and Example 1 is that the preparation method of the modified nanomaterial is different.

[0059] A composition containing p-tert-butylbenzoic acid comprises the following components in parts by weight: 3 parts of sodium dodecylbenzene sulfonate, 1.5 parts of glycerol, 1.3 parts of polyisobutylene, 6 parts of modified walnut shells, 3.6 parts of ammonium molybdate, 1.4 parts of polyethylene glycol, 3 parts of diethanolamine, 2 parts of oleic acid, 5 parts of p-tert-butylbenzoic acid, 5.4 parts of monoethanolamine benzoate, 0.12 parts of sodium lauryl sulfate, 12.6 parts of polyvinyl chloride latex, 4 parts of tetrazole, 1.4 parts of modified nanomaterials and 200 parts of deionized water.

[0060] The preparation method of the modified nano material is as follows: the nano material, 55wt% ethanol aqueous solution and modified silane coupling agent are mixed in a mass ratio of 1:7:0.02, stirred at 60°C for 4h, filtered to obtain a solid, and then washed and dried.

[0061] The nanomaterials are nano-aluminum oxide, nano-silicon carbide and nano-lanthanum oxide in a mass ratio of 1:1.2:0.7.

[0062] The preparation method of modified walnut shell is: (1) crushing dried walnut shells, adding them to a sodium hydroxide aqueous solution 6 times the mass of the walnut shells, heating them to 128° C. at a pressure of 0.27 MPa and keeping the temperature for 125 min to obtain a first solution; (2) After the first solution is cooled to 67° C., a sulfuric acid aqueous solution in an amount 4 times the mass of the walnut shells is added thereto, and the solution is kept warm for 38 minutes at a pressure of 0.27 MPa to obtain a second solution; (3) washing the second solution with deionized water until it is neutral, centrifuging, and drying to obtain the initially treated walnut shells; (4) The walnut shells after the initial treatment are moistened with water and placed in a microwave field for microwave treatment to obtain modified walnut shells.

[0063] The dried walnut shells were crushed to 300 mesh.

[0064] The concentration of the sodium hydroxide aqueous solution is 38%.

[0065] The concentration of the aqueous sulfuric acid solution is 45%.

[0066] Centrifuge at 2400 rpm for 4 min.

[0067] The mixture was treated with a microwave at 370 W for 3 min.

[0068] The preparation method of the composition is: (1) Weigh the raw materials of each component according to the above mass percentage and set aside; (2) First, the modified walnut shell, tert-butylbenzoic acid, polyisobutylene and polyvinyl chloride latex were mixed, heated to 52°C, and stirred at a speed of 170 r / min for 18 min until transparent; (3) Then add monoethanolamine benzoate and mix, raise the temperature to 61°C, and stir at a speed of 125 r / min for 9 minutes; (4) Finally, add water and mix, raise the temperature to 62°C, stir at 100 r / min for 4 min, and cool naturally to room temperature.

[0069] Comparative Example 3 The difference between this comparative example and Example 1 is that the nanomaterial composition is different.

[0070] A composition containing p-tert-butylbenzoic acid comprises the following components in parts by weight: 3 parts of sodium dodecylbenzene sulfonate, 1.5 parts of glycerol, 1.3 parts of polyisobutylene, 6 parts of modified walnut shells, 3.6 parts of ammonium molybdate, 1.4 parts of polyethylene glycol, 3 parts of diethanolamine, 2 parts of oleic acid, 5 parts of p-tert-butylbenzoic acid, 5.4 parts of monoethanolamine benzoate, 0.12 parts of sodium lauryl sulfate, 12.6 parts of polyvinyl chloride latex, 4 parts of tetrazole, 1.4 parts of modified nanomaterials and 200 parts of deionized water.

[0071] The preparation method of the modified nanomaterial is: (1) Mix 1 part of nanomaterial and 11 parts of water, add sodium carbonate to make the pH value 9.5, and stir at 62°C for 2.4 hours to form a nanomaterial suspension; (2) Add 0.3 parts of hexadecyltrimethylammonium bromide to 10 parts of the nanomaterial suspension, mix well, stir, react at 56° C. for 2.6 hours, filter, wash, dry, and grind to obtain modified nanomaterials.

[0072] The nanomaterials are nano-aluminum oxide, nano-silicon carbide and nano-lanthanum oxide in a mass ratio of 1:1:1.

[0073] The preparation method of modified walnut shell is: (1) crushing dried walnut shells, adding them to a sodium hydroxide aqueous solution 6 times the mass of the walnut shells, heating them to 128° C. at a pressure of 0.27 MPa and keeping the temperature for 125 min to obtain a first solution; (2) After the first solution is cooled to 67° C., a sulfuric acid aqueous solution in an amount 4 times the mass of the walnut shells is added thereto, and the solution is kept warm for 38 minutes at a pressure of 0.27 MPa to obtain a second solution; (3) washing the second solution with deionized water until it is neutral, centrifuging, and drying to obtain the initially treated walnut shells; (4) The walnut shells after the initial treatment are moistened with water and placed in a microwave field for microwave treatment to obtain modified walnut shells.

[0074] The dried walnut shells were crushed to 300 mesh.

[0075] The concentration of the sodium hydroxide aqueous solution is 38%.

[0076] The concentration of the aqueous sulfuric acid solution is 45%.

[0077] Centrifuge at 2400 rpm for 4 min.

[0078] The mixture was treated with a microwave at 370 W for 3 min.

[0079] The preparation method of the composition is: (1) Weigh the raw materials of each component according to the above mass percentage and set aside; (2) First, the modified walnut shell, tert-butylbenzoic acid, polyisobutylene and polyvinyl chloride latex were mixed, heated to 52°C, and stirred at a speed of 170 r / min for 18 min until transparent; (3) Then add monoethanolamine benzoate and mix, raise the temperature to 61°C, and stir at a speed of 125 r / min for 9 minutes; (4) Finally, add water and mix, raise the temperature to 62°C, stir at 100 r / min for 4 min, and cool naturally to room temperature.

[0080] Comparative Example 4 The difference between this comparative example and Example 1 is that no modified walnut shell is added.

[0081] A composition containing p-tert-butylbenzoic acid comprises the following components in parts by weight: 3 parts of sodium dodecylbenzene sulfonate, 1.5 parts of glycerol, 1.3 parts of polyisobutylene, 3.6 parts of ammonium molybdate, 1.4 parts of polyethylene glycol, 3 parts of diethanolamine, 2 parts of oleic acid, 5 parts of p-tert-butylbenzoic acid, 5.4 parts of monoethanolamine benzoate, 0.12 parts of sodium lauryl sulfate, 12.6 parts of polyvinyl chloride latex, 4 parts of tetrazole, 1.4 parts of modified nanomaterials and 200 parts of deionized water.

[0082] The preparation method of the modified nanomaterial is: (1) Mix 1 part of nanomaterial and 11 parts of water, add sodium carbonate to make the pH value 9.5, and stir at 62°C for 2.4 hours to form a nanomaterial suspension; (2) Add 0.3 parts of hexadecyltrimethylammonium bromide to 10 parts of the nanomaterial suspension, mix well, stir, react at 56° C. for 2.6 hours, filter, wash, dry, and grind to obtain modified nanomaterials.

[0083] The nanomaterials are nano-aluminum oxide, nano-silicon carbide and nano-lanthanum oxide in a mass ratio of 1:1.2:0.7.

[0084] The preparation method of the composition is: (1) Weigh the raw materials of each component according to the above mass percentage and set aside; (2) First, tert-butylbenzoic acid, polyisobutylene and polyvinyl chloride latex were mixed, heated to 52°C, and stirred at a speed of 170 r / min for 18 min until transparent; (3) Then add monoethanolamine benzoate and mix, raise the temperature to 61°C, and stir at a speed of 125 r / min for 9 minutes; (4) Finally, add water and mix, raise the temperature to 62°C, stir at 100 r / min for 4 min, and cool naturally to room temperature.

[0085] Comparative Example 5 The difference between this comparative example and Example 1 is that the walnut shell is not modified.

[0086] A composition containing p-tert-butylbenzoic acid comprises the following components in parts by weight: 3 parts of sodium dodecylbenzene sulfonate, 1.5 parts of glycerol, 1.3 parts of polyisobutylene, 6 parts of walnut shells, 3.6 parts of ammonium molybdate, 1.4 parts of polyethylene glycol, 3 parts of diethanolamine, 2 parts of oleic acid, 5 parts of p-tert-butylbenzoic acid, 5.4 parts of monoethanolamine benzoate, 0.12 parts of sodium lauryl sulfate, 12.6 parts of polyvinyl chloride latex, 4 parts of tetrazole, 1.4 parts of modified nanomaterials and 200 parts of deionized water.

[0087] The preparation method of the modified nanomaterial is: (1) Mix 1 part of nanomaterial and 11 parts of water, add sodium carbonate to make the pH value 9.5, and stir at 62°C for 2.4 hours to form a nanomaterial suspension; (2) Add 0.3 parts of hexadecyltrimethylammonium bromide to 10 parts of the nanomaterial suspension, mix well, stir, react at 56° C. for 2.6 hours, filter, wash, dry, and grind to obtain modified nanomaterials.

[0088] The nanomaterials are nano-aluminum oxide, nano-silicon carbide and nano-lanthanum oxide in a mass ratio of 1:1.2:0.7.

[0089] The preparation method of walnut shell is as follows: the dried walnut shell is crushed into 300 meshes.

[0090] The preparation method of the composition is: (1) Weigh the raw materials of each component according to the above mass percentage and set aside; (2) First, walnut shells, p-tert-butylbenzoic acid, polyisobutylene, and polyvinyl chloride latex were mixed, heated to 52°C, and stirred at a speed of 170 r / min for 18 min until transparent; (3) Then add monoethanolamine benzoate and mix, raise the temperature to 61°C, and stir at a speed of 125 r / min for 9 minutes; (4) Finally, add water and mix, raise the temperature to 62°C, stir at 100 r / min for 4 min, and cool naturally to room temperature.

[0091] Performance Testing With reference to GB6144-85, the properties of the compositions of Examples 1-3 and Comparative Examples 1-5 were measured.

[0092] Table 1 Performance test results

[0093] It can be seen from Table 1 that the coating of the present invention has excellent anti-corrosion and anti-rust effects.

[0094] By comparing Example 1 with Comparative Examples 1 to 3, it can be seen that the modified nanomaterial described in the present invention can significantly improve the anti-corrosion and anti-rust effects, and the modified nanomaterial prepared by the preparation method of the present invention can significantly improve the anti-corrosion and anti-rust effects.

[0095] By comparing Example 1 with Comparative Examples 4-5, it can be seen that the present invention significantly improves the anti-corrosion and anti-rust effects by modifying the walnut shell.

[0096] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A composition containing p-tert-butylbenzoic acid, characterized in that, The composition comprises the following components in parts by weight: 2-4 parts of sodium dodecylbenzene sulfonate, 1-2 parts of glycerol, 1-2 parts of polyisobutylene, 5-7 parts of modified walnut shells, 3-4 parts of ammonium molybdate, 1-2 parts of polyethylene glycol, 2-4 parts of diethanolamine, 1-3 parts of oleic acid, 4-6 parts of p-tert-butylbenzoic acid, 5-6 parts of monoethanolamine benzoate, 0.06-0.18 parts of sodium lauryl sulfate, 12-13 parts of polyvinyl chloride latex, 3-5 parts of tetrazole, 1-2 parts of modified nanomaterials and 200 parts of deionized water.

2. The composition containing p-tert-butylbenzoic acid according to claim 1, characterized in that The preparation method of the modified nanomaterial is: (1) Mix 1 part of nanomaterial with 10-12 parts of water, add sodium carbonate to make the pH value 9-10, and stir at 60-64°C for 2-3 hours to form a nanomaterial suspension; (2) Add 0.2-0.4 parts of hexadecyltrimethylammonium bromide to 10 parts of the nanomaterial suspension, mix well, stir, react at 55-60° C. for 2-3 hours, filter, wash, dry, and grind to obtain a modified nanomaterial.

3. The composition containing p-tert-butylbenzoic acid according to claim 2, characterized in that The nano materials are nano aluminum oxide, nano silicon carbide and nano lanthanum oxide in a mass ratio of 1:1.2-1.3:0.6-0.

7.

4. The composition containing p-tert-butylbenzoic acid according to claim 1, characterized in that The preparation method of modified walnut shell is: (1) crushing dried walnut shells, adding them to a sodium hydroxide aqueous solution 5-6 times the mass of the walnut shells, heating them to 125-130° C. at a pressure of 0.26-0.29 MPa and keeping the temperature for 120-130 minutes to obtain a first solution; (2) After the first solution is cooled to 65-70° C., a sulfuric acid aqueous solution in an amount 3-4 times the mass of the walnut shells is added thereto, and the solution is kept warm for 35-40 minutes at a pressure of 0.26-0.28 MPa to obtain a second solution; (3) washing the second solution with deionized water until it is neutral, centrifuging, and drying to obtain the initially treated walnut shells; (4) The walnut shells after the initial treatment are moistened with water and placed in a microwave field for microwave treatment to obtain modified walnut shells.

5. The composition containing p-tert-butylbenzoic acid according to claim 4, characterized in that The dried walnut shells were crushed to 200-300 mesh.

6. The composition containing p-tert-butylbenzoic acid according to claim 4, characterized in that The concentration of the sodium hydroxide aqueous solution is 37-39%.

7. The composition containing p-tert-butylbenzoic acid according to claim 4, characterized in that The concentration of the aqueous sulfuric acid solution is 43-48%.

8. The composition containing p-tert-butylbenzoic acid according to claim 4, characterized in that Centrifuge at 2300-2500r / min for 3-5min.

9. The composition containing p-tert-butylbenzoic acid according to claim 4, characterized in that The mixture was treated with a microwave at 350-400 W for 2-3 min.

10. Use of a composition containing p-tert-butylbenzoic acid according to any one of claims 1 to 9 in the preparation of a fully synthetic cutting fluid.

Citation Information

Patent Citations

  • Rustproof metal cutting fluid and preparation method thereof

    CN103351934A

  • Cutting fluid with high performance suitable for usage of metal and preparation method thereof

    CN104109579A

  • Oxidation corrosion-resistant nanometer aluminum nitride transformer oil containing pine tar, and preparation method thereof

    CN104212549A

  • Environment-friendly anti-rust metal cutting fluid

    CN106753739A